Kotaka’s Model in land acquisition for infrastructure provision in Malaysia - Omar, Ismail; Ismail, Mazlan (Emerald Group Publishing Limited, 2009)
Purpose – The purpose of this paper is to explain the definition of adequate compensation from the viewpoints of affected landowners, property valuers and land administrators using Kotaka’s Model with special application in Kedah, Malaysia.The fact is that land is a factor of production and must be made available for the provision of infrastructure.In acquiring land for real estate development, compensation must be paid to the affected landowners.An adequate compensation in land acquisition is referred to the open market value of the land taken plus its consequences including severance, injurious affection and disturbances.Design/methodology/approach – Questionnaires are distributed to the affected 40 landowners,ten property valuers and six land administrators of randomly selected land acquisition projects for public infrastructure land development in the case study areas.Data gathered are analyzed using qualitative descriptive analysis to identify elements of dissatisfactions of landowners upon compensation offered to them.Findings – The findings show that there are elements of dissatisfactions to the affected landowners by way of the value of land taken, severances, injurious affections, disturbances, delivery of notices and technique of valuation. These dissatisfactions reflect the amount of adequate compensation to the affected landowners and cross-examined with property valuers and land administrators. Originality/value – The outcome of the paper will assist landowners, public, and private valuers, land administrators and other stakeholders to understand the elements of dissatisfactions in estimating adequate compensation in land acquisition for infrastructure provision.Otherwise, the affected landowners may refuse to be apart from their lands, hence, restrict the flow of land supply for real estate development.This indicates that Kotaka’s Model offers an explanatory power to understand the elements of adequate compensation in land acquisition for infrastructure provision and real estate development.